Fostering the practice of communicative competence in ESL classrooms - Choudhury, Shaheena (BRAC University, 2010)
In an attempt to make our students literate in international discourse, to make them compete successfully on a national and international level, the demand to teach communicative English is increasing more and more in Bangladesh. Recognizing the fact that English communication abilities can only be formed when students are taught English by applying the Communicative Language Teaching method in English, most of our educational institutions are following the trend, but with little or no success, since students are failing to develop an acceptable level of English proficiency for communication. This paper begins by exploring a number of theories of communicative competence. It investigates the condition of communicative language teaching in the universities of Bangladesh and discusses the need for teachers' training. It further reviews a survey conducted with participants currently enrolled in the different departments of Brac University, to find some of the major problems encountered by them in ESL classes which affect their speaking abilities. Based on the findings, different ways of promoting oral communication in language classes have been recommended.